Comparison of Habitat Suitability Models for Haemaphysalis longicornis Neumann in North America to Determine Its Potential Geographic Range - Namgyal, Jamyang; Couloigner, Isabelle; Lysyk, Tim J.; Dergousoff, Shaun J.; Cork, Susan C. (International journal of environmental research and public health, 2020)
Haemaphysalis longicornis Neumann, 1901 is a vector of many pathogens of public and veterinary health importance in its native range in East Asia and introduced range in Oceania. In North America, this tick was first detected in New Jersey in 2017. Currently, this tick has been reported from 15 states of the United States. In this study, we modeled the habitat suitability of H. longicornis using the MaxEnt modeling approach. We separated occurrence records from the published literature from four different geographical regions in the world and developed MaxEnt models using relevant environmental variables to describe the potential habitat suitability of this tick in North America. The predictive accuracy of the models was assessed using the U.S. county locations where this tick species has been reported. Our best model predicted that the most suitable North American areas for geographic expansion of H. longicornis are from Arkansas–South Carolina to the south of Quebec–Nova Scotia in the east, and from California to the coast of British Columbia in the west. Enhanced surveillance and further investigation are required to gain a better understanding of the role that this tick might play in the transmission of diseases to humans and animals in North America.